Reverse shoulder arthroplasty: diagnostic and treatment options for the infected reverse - Stone, Michael A.; Namdari, Surena (Annals of Joint; Vol 3 (November 2018): Annals of Joint, 2018)
Infection in the setting of reverse total shoulder arthroplasty (RTSA) can be a devastating complication. Revision for infection in RTSA has the worst functional outcomes for any reason for revision. A consensus for the definition of a periprosthetic shoulder infection has yet to be defined, and diagnostic techniques are variable. Options for treatment include irrigation and debridement with component retention, one-stage revision, two-stage revision, and resection arthroplasty. There is no gold standard for treatment and decisions are made based on multiple factors, including bacterial species, medical comorbidities, and patient expectations.